The Tragedy of macbeth - Shakespeare, William (Sweet Cherry Publishing UK, 2013)
"The Tragedy of Macbeth" is a Shakespearean play that explores the destructive effects of ambition and guilt, as Macbeth$1 (Bs rise to power leads to his downfall and ultimate demise.s